Interaction between prion protein and toxic amyloid ß assemblies can be therapeutically targeted at multiple sites. - KLYUBIN, IGOR; ROWAN, MICHAEL (My University, 2011)
A role for PrP in the toxic effect of oligomeric forms of A?, implicated in Alzheimer's disease (AD), has been suggested but remains controversial. Here we show that PrP is required for the plasticity-impairing effects of ex vivo material from human AD brain and that standardized A?-derived diffusible ligand (ADDL) preparations disrupt hippocampal synaptic plasticity in a PrP-dependent manner. We screened a panel of anti-PrP antibodies for their ability to disrupt the ADDL?PrP interaction. Antibodies directed to the principal PrP/A?-binding site and to PrP helix-1, were able to block A? binding to PrP suggesting that the toxic A? species are of relatively high molecular mass and/or may bind multiple PrP molecules. Two representative and extensively characterized monoclonal antibodies directed to these regions, ICSM-35 and ICSM-18, were shown to block the A?-mediated disruption of synaptic plasticity validating these antibodies as candidate therapeutics for AD either individually or in combination.
PUBLISHED
Keywords: Neuroscience; Alzheimer's disease (AD); Ageing; Neuroscience